The Determination of Factors That Affect on the Durability of Reinforced Concrete of the Contact Network - Kuznetsov, V. H.; Poliakh, O. M. (Science and Transport Progress, 2007)
The authors determined the factors, which have impact on durability of contakt lines racks. The numeric characteristics of thicknesses of concrete racks are counted.